PENGARUH MENGKONSUMSI JUS BUAH STROBERI DALAM MENGHAMBAT PERTUMBUHAN KOLONI BAKTERI SALIVA RONGGA MULUT - Niken Probosari; Dyah Setyorini; Tia Novianti (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Flow of saliva constitute certain natural process which be able cleansing food residue from teeth surface and for the same time to protect mouth tissue from bacteria influence. One of fruits contains much nutrition is strawberry. Strawberry fruit is contain of xylitol have characteristic to obstruct growth of bacteria in oral cavity.This research as a purpose for find out influence consumption strawberry juice toward amount growth colony of saliva bacteria in the oral cavity. Research of subject have 16people from the population which take with purposive sampling method. Result of data research on test with Kolmogorov-Smirnov and Levene test to find out which data distribution normal and homogeneous, Furthermore with parametric test analisis varians one way with level of trust 95%(α=0,005). Furhermore with Tukey-HSD test. Result from this research with consumption beverage of strawberry juice can reduse amount colony of saliva bacteria and can obstruct growth colonybacteria in the oral cavity.